2010
DOI: 10.1001/archophthalmol.2010.157
|View full text |Cite
|
Sign up to set email alerts
|

Punctate Inner Choroidopathy

Abstract: To describe the clinical features and outcomes of a large group of patients with a spectrum of clinical appearances and diagnosed as having punctate inner choroidopathy (PIC).Methods: In a retrospective consecutive case series, patients seen during a 16-year period at Moorfields Eye Hospital who were diagnosed as having PIC and had a minimum of 12 months' follow-up were included. Patients were classified as having typical PIC or atypical PIC (larger, presumed ocular histoplasmosis syndrome-like lesions). Main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 10 publications
1
22
0
2
Order By: Relevance
“…No significant differences in demographics and clinical outcomes were identified between the two groups. They reported that presence of PIC lesions in fellow eyes of patients with unilateral CNV was a risk factor for development of CNV in the fellow eyes as well [14], hence emphasizing the importance of immediately identifying and treating any recurrence in disease activity. Previously, we have shown that the employment of IMT such as mycophenolate mofetil may help to decrease the frequency of attacks in recurrent PIC disease [4].…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences in demographics and clinical outcomes were identified between the two groups. They reported that presence of PIC lesions in fellow eyes of patients with unilateral CNV was a risk factor for development of CNV in the fellow eyes as well [14], hence emphasizing the importance of immediately identifying and treating any recurrence in disease activity. Previously, we have shown that the employment of IMT such as mycophenolate mofetil may help to decrease the frequency of attacks in recurrent PIC disease [4].…”
Section: Discussionmentioning
confidence: 99%
“…This disease tends to occur in young, myopic women and is associated with the development of choroidal neovascularization and subsequent vision loss [174]. …”
Section: White Dot Syndromesmentioning
confidence: 99%
“…7,[14][15][16] Essex et al, 2 in the largest series of patients diagnosed with PIC, reported a total of 153 eyes of 117 patients with PIC-related choroidal neovascular membranes; 26% of those eyes had a final visual acuity of less than 1/10. The final outcome was similar in all groups with choroidal neovascular membrane, regardless of the treatment; however, in this series none of the patients were treated with anti-VEGF agents.…”
Section: Diagnosis and Discussionmentioning
confidence: 99%
“…2 The symptoms are usually unilateral, but most patients show bilateral fundus involvement. 2,3 PIC is characterized by multifocal choroidal lesions (yellow-white lesions of the inner choroid and retinal pigment epithelium of approximately 100-300 μm in size), usually distributed throughout the posterior pole but sparing the peripapillary region. 2,4 There are no other signs of ocular inflammation elsewhere in the eye.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation